If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1.2(y + -3) = -0.7(y + -1) Reorder the terms: -1.2(-3 + y) = -0.7(y + -1) (-3 * -1.2 + y * -1.2) = -0.7(y + -1) (3.6 + -1.2y) = -0.7(y + -1) Reorder the terms: 3.6 + -1.2y = -0.7(-1 + y) 3.6 + -1.2y = (-1 * -0.7 + y * -0.7) 3.6 + -1.2y = (0.7 + -0.7y) Solving 3.6 + -1.2y = 0.7 + -0.7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '0.7y' to each side of the equation. 3.6 + -1.2y + 0.7y = 0.7 + -0.7y + 0.7y Combine like terms: -1.2y + 0.7y = -0.5y 3.6 + -0.5y = 0.7 + -0.7y + 0.7y Combine like terms: -0.7y + 0.7y = 0.0 3.6 + -0.5y = 0.7 + 0.0 3.6 + -0.5y = 0.7 Add '-3.6' to each side of the equation. 3.6 + -3.6 + -0.5y = 0.7 + -3.6 Combine like terms: 3.6 + -3.6 = 0.0 0.0 + -0.5y = 0.7 + -3.6 -0.5y = 0.7 + -3.6 Combine like terms: 0.7 + -3.6 = -2.9 -0.5y = -2.9 Divide each side by '-0.5'. y = 5.8 Simplifying y = 5.8
| 2y+11=5y-7 | | X^2-11=38 | | 8[2+7(8+6)]= | | 8-2y+2y=8 | | -2(x+3)+3=3(x+3)+6 | | 10+7x=16+x | | -5x+6=5x-4 | | -2(4v+4)=-8v+7 | | -3(-5-5)=15w-20 | | 0.1x-0.1(5-x)=0.8 | | 4+10x=13+x | | 3(6y-7)-14=y-2(5y+4) | | -5d+3=-2d-27 | | 4x-6=2x+22 | | -3x-8(19-15x)=20 | | 6x-4(3-x)=12 | | 1-5a^2+2a+4a= | | 2.50+x+x+x+x=14.30 | | 4(2y+5)=44 | | 16(x-7)=-8-8 | | x^2-9x^2+20=0 | | 18x=42 | | 0=ln(x+2)+ln(x-2) | | .0=11.1-n | | v^2-v^2+6v= | | (6x-3)-[5+(-9x+3)]=6x-1 | | 56x+62x=58.80 | | 10x+6=4x+60 | | -8p+32-2p=112 | | (Z^2+35)=(12z-1) | | y+6y^2-2y-4y= | | 4p^2-6=19 |